PENGAWASAN OMBUDSMAN DALAM PENYELENGGARAAN PELAYANAN PUBLIK BERDASARKAN UNDANG-UNDANG NOMOR 25 TAHUN 2009 - Siti Hasanah; Idea Islami Parasatya (Universitas Muhammadiyah Mataram, 2019)
This paper discusses the supervision of the Ombudsman in the implementation of public services. The state is obliged to provide public services to every citizen as a form of the constitutional mandate. The duty of public service is carried out by the State Civil Apparatus. In the practice of carrying out the functions and authorities of public services to the people carried out by the State Civil Apparatus, they have not been maximally normative based on Law number 25 of 2009, as well as implement natively. Research is Normative legal research using descriptive qualitative methods and secondary data studies from several collections of literature studies. The results of the study show that the behavior and service patterns of the State Civil Apparatus still deviate a lot from what they should, even though they have been escorted through legal instruments, both in the form of regulations, technical instructions and implementing instructions as a legal umbrella and reference to the implementation of their functions and authorities. Internal control by the relevant agencies does not seem to have been able to be a solution in solving problems of poor quality public services. This pattern, if allowed to roll out, will have an impact on the failure to realize a sound system of public service delivery by the general principles of government and corporation. The presence of the Ombudsman Commission of the Republic of Indonesia is a solution to maximize the function of public services by the State Civil Apparatus.Keywords: ombudsman; public services; supervision.Tulisan ini membahas tentang pengawasan Ombudsman dalam pelaksanaan pelayanan publik. Negara berkewajiban untuk memberikan layanan publik kepada setiap warga negara sebagai bentuk amanat konstitusi. Tugas pelayanan publik dilakukan oleh Aparatur Sipil Negara. Dalam praktik menjalankan fungsi dan wewenang pelayanan publik kepada orang-orang yang dilakukan oleh Aparatur Sipil Negara, mereka belum secara normatif maksimal berdasarkan UU No. Penelitian adalah penelitian hukum normatif menggunakan metode deskriptif kualitatif dan studi data sekunder dari beberapa kumpulan studi literatur. Hasil penelitian menunjukkan bahwa perilaku dan pola pelayanan Aparatur Sipil Negara masih menyimpang dari apa yang seharusnya, meskipun mereka telah dikawal melalui instrumen hukum, baik dalam bentuk peraturan, instruksi teknis dan instruksi pelaksanaan sebagai payung hukum dan referensi untuk pelaksanaan fungsi dan wewenang mereka. Pengendalian internal oleh instansi terkait tampaknya tidak mampu menjadi solusi dalam menyelesaikan masalah buruknya layanan publik. Pola ini, jika dibiarkan, akan berdampak pada kegagalan mewujudkan sistem pemberian layanan publik yang baik sesuai dengan prinsip umum pemerintah dan korporasi. Kehadiran Komisi Ombudman Republik Indonesia merupakan solusi untuk memaksimalkan fungsi pelayanan publik oleh Aparatur Sipil Negara.Kata kunci: layanan publik; ombudsman; pengawasan.